EP226 The advancing age: breast cancer over 80 years. (1st November 2019) - Rocha, AC; Sá, MI; Raposo, S; Sousa, R; Correia, P; Aldinhas, P; Branco, E; Coelho, C; Baltar, V; Sá, L
Abstract : Introduction/Background: Improvements in health care have resulted in a gain in overall life expectancy. Breast cancer is the most common cancer in women, with an incidence that increases with advancing age. However, older women may exhibit a variety of clinical presentations that may influence the treatment and prognosis of this disease. Methodology: A retrospective cohort study with 130 women aged ≥80 years with breast cancer, referred to the gynaecology appointment of the IPO-Coimbra (2013 and 2018). The information was treated in SPSS DATA editor version 15.0. Statistical significance was set at p<0.05. Results: The mean age was 83 years. During the study period, 983 women had breast cancer, of which 130 women were aged >80 years. In terms of the comorbilities, 73.8% presented with HBP and 23.8% DM. The most frequent stage at diagnosis was T2 N0 M0. Regarding the therapy performed, only 9.2% performed neoadjuvant therapy (between hormone therapy (HT) and/or radiotherapy (RT)). In surgical terms, 60.8% underwent surgery and, in most cases (78.5%), no conservative surgery was performed. As regards to adjuvant therapy, 56.7% of the patients performed some type of therapy (RT, HT and/or chemotherapy (QT)). Palliative care was offered to 16.9% of patients as a primary therapy. Concerning the general prognosis, 7.9% of the patients relapsed, but only 10.8% had cancer-related mortality, with a median disease-free time of 16 months. The χ2 test did not show a statistically significant association between mortality and age when analyzed by age group (p=0.32). Conclusion: This patients represent an expanding group with specific characteristics that may influence the treatment and prognosis of breast cancer. However, there aren't enough studies to define strategies in this age group. Therefore, it would be important to implement multicenter studies in order to overcome this limitation. Disclosure: Nothing to disclose.